2015
DOI: 10.1002/2015jd023184
|View full text |Cite
|
Sign up to set email alerts
|

Subseasonal variations in spatial signatures of ENSO on the Indian summer monsoon from 1901 to 2009

Abstract: Correlations of 1 ∘ by 1 ∘ seasonal rainfall with Pacific sea surface temperatures (SSTs) reveal spatially distinct teleconnections between El Niño-Southern Oscillation (ENSO) and Indian summer monsoon rainfall over the full monsoon season, as well as three subseasons. Over the full season (June-September), Pacific SSTs correlate with rainfall in Western India more than that in Eastern India. This spatial signature shifts as the monsoon progresses through early (June), middle or peak (July-August), and late (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…In addition, the monsoon system is a critical component in the “seamless” multiscale climate system. The relations between the Indian summer monsoon and major climate modes (such as ENSO and IODZM) are still being debated (Ashok et al, ; Gill et al, ; Kumar et al, ; Sabeerali et al, ). The CIO mode, as a climate mode mainly at intraseasonal timescales and with pronounced seasonal and interannual variabilities, provides a new avenue to pinpoint the role of the Indian Ocean and the Indian summer monsoon in the climate system and helps to reveal the relationship between the Indian summer monsoon and other climate processes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the monsoon system is a critical component in the “seamless” multiscale climate system. The relations between the Indian summer monsoon and major climate modes (such as ENSO and IODZM) are still being debated (Ashok et al, ; Gill et al, ; Kumar et al, ; Sabeerali et al, ). The CIO mode, as a climate mode mainly at intraseasonal timescales and with pronounced seasonal and interannual variabilities, provides a new avenue to pinpoint the role of the Indian Ocean and the Indian summer monsoon in the climate system and helps to reveal the relationship between the Indian summer monsoon and other climate processes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In addition, a better understanding of MISO also has an obvious scientific and socioeconomic significance for the livelihood of billions of people living on the rim of the Indian Ocean. To date, the predictability of monsoon rainfall remains low (Wang et al, ), which is attributable to the much‐debated relationship between MISO and the major intrinsic climate modes, such as ENSO (e.g., Gill et al, ; Kumar et al, ) and the Indian Ocean Dipole‐Zonal Mode (IODZM) (e.g., Ashok et al, ; Kripalani & Kumar, ; Murtugudde & Busalacchi, ; Murtugudde et al, ). Recently, a central Indian Ocean (CIO) mode, which is defined using a combination of intraseasonal sea surface temperature (SST) anomalies and intraseasonal low‐level wind anomalies over the Indian Ocean, was found to have a close relation with monsoonal rainfall (Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Weakening of the Indian summer monsoon produces less precipitation and droughts whereas the stronger La Niña monsoon produces enhanced precipitation [92,93]. The observed correlation between ENSO and the monsoon does not, however, guarantee a weakening of the Indian summer monsoon during an El Niño event due to the statistical nature of the relationship [80,93,94]. Elucidating a clearer understanding of the dynamical relationship between ENSO and the monsoon is important, as it is one of the important factors governing precipitation over the glaciers in the Karakoram Himalaya.…”
Section: El Niño-southern Oscillation (Enso)mentioning
confidence: 82%
“…In an area with a strong ENSO teleconnection, Gill et al . () found notable teleconnection asymmetries implying important variations in signal strength and direction by region and sub‐seasons. In other words, detecting a strong ENSO warm episode does not imply that its opposite phase (ENSO cool episode) will occur with the same intensity, at the same region or in the same season.…”
Section: Introductionmentioning
confidence: 80%
“…Yet, assuming the same level of teleconnection at each and every place on Earth would also be misleading, because the ENSO signal varies in magnitude and direction at different spatial and temporal scales. In an area with a strong ENSO teleconnection, Gill et al (2015) found notable teleconnection asymmetries implying important variations in signal strength and direction by region and sub-seasons. In other words, detecting a strong ENSO warm episode does not imply that its opposite phase (ENSO cool episode) will occur with the same intensity, at the same region or in the same season.…”
Section: Introductionmentioning
confidence: 91%